Enhancing genetic variability in Solanum surattense (Burm.f.) through EMS and gamma ray-induced mutagenesis - Srinivasu, Pathakakula; Nalina, Lakshmanan; Saraswathi , Thiruvenkatasamy; Geethanjali, Subramaniam; Manikanda Boopathi, Narayanan; Chandrakumar, Kalichamy; Meenakumari, Balakrishnan (Plant Science Today, 2025)
Solanum surattense Burm.f. is an important medicinal plant with limited genetic variability due to presence of heavy thorns. The objective of this study represents the first report on the induction of mutation in Solanum surattense Burm.f. using EMS and gamma ray irradiation to enhance its genetic variation. A total of 100 pre-soaked Kantakari seeds were treated with varying concentrations of EMS (0.2 %, 0.4 %, 0.6 %, 0.8 % and 1 %), gamma rays (50 Gy, 100 Gy, 150 Gy, 200 Gy and 250 Gy) and their combined treatments (50 Gy + 0.2 % EMS, 100 Gy + 0.4 % EMS, 50 Gy + 0.6 % EMS, 200 Gy + 0.8 % EMS and 250 Gy + 1 % EMS). The results revealed a progressive decline in germination rate, survival percentage, root length (cm) and shoot length (cm) with increasing doses of both individual and combined mutagens in the M1 generation. The LD50 values were determined as 0.8 % EMS (47.48 %), 200 Gy gamma rays (46.47 %) and a combination treatment of 0.4 % EMS + 100 Gy (53.54 %). Mutation breeding using gamma rays, EMS and their combinations significantly influenced growth and yield parameters, in addition to, reducing thorn density. Among the tested treatments, the combination of 0.4 % EMS + 100 Gy (6.23, 5.42) and 200 Gy gamma rays (8.69, 7.31) was the most effective in reducing the number of thorns on both the upper and lower surfaces of the leaves. These findings suggest that mutation breeding through gamma irradiation and combination treatments holds great potential for developing high-yielding, low-thorn mutants of Kantakari, making it a valuable approach for future crop improvement programs.